A Mutual Language Policy: Facilitating Shared Interests between Foreign and Indigenous Workers Regarding Language, Socio-culture, Ideology and Identity - Fathiaty Murtadho; Fernandes Arung; Endry Boeriswati; Reni Nur Eriyani; Miftahulkhairah Anwar; Asep Supriyana (Jurnal Gramatika, 2024)
We propose a Mutual Language Policy to mediate shared interests between Chinese and indigenous workers in minimalizing frictions related to language attitudes, socio-cultural attitudes, ideologies and identities. So far, language policy has only sided with indigenous interests initiated by the government and has not involved foreign interests. By using multiple case study, we analyzed language attitudes, socio-cultural attitudes, as well as ideologies and identities of Chinese and indigenous workers to understand the frictions that occurred. We found that the language attitude of the Chinese workers was considered positive while the dominant use of Mandarin was only caused by the lack of mastery of both Indonesian and English. Next, the socio-cultural attitude of Chinese workers that seemed exclusive was basically caused by two main things,firstly, their concern about counterculture and contra behavior towards indigenous people.Secondly, the social class in employment context. Finally, the defense of the ideology and identity of the indigenous community seemed so strong was because of the collective defense system. Shared interests among them in a mutual language policy concept are also discussed.